Comprehensive Composition of Flavor Precursors in Kopi Luwak and Jacu Exotic Green Bioprocessed Coffees - Ripper, Beatriz; Barreto, Maysa Silva; Novaes, Fabio Junior Moreira; de Godoy, Mateus Gomes; Freire, Denise Maria Guimarães; de Rezende, Claudia Moraes; Nunes, Juliana Cortes; Perrone, Daniel (Frontiers in Sustainable Food Systems, 2022)
Exotic coffees may be defined as extravagant and unique coffees, primarily due to their production mode, including unusual bioprocessing or fermentation conditions associated with superior sensorial characteristics. The aim of the present study was to investigate the influence of bioprocessing and of growing conditions on flavor precursors of Jacu and Kopi Luwak exotic green coffees, respectively. Moreover, this is the first study to perform a detailed chemical analysis of these exotic coffees. Thirteen green Coffea arabica bean samples were obtained, five from Espírito Santo state, Brazil, and eight Kopi Luwak from different regions of Indonesia. Samples were analyzed regarding their proximate composition, chlorogenic acids (CGA), sucrose, alkaloids, triacylglycerols (TAG), diacylglycerols, free fatty acids, sterols, diterpenes and tocopherols. Scanning electron micrography confirmed bioprocessing of Jacu and Kopi Luwak coffee samples. Bioprocessing by the Jacu bird caused reductions of 69% and 28% in caffeine and CGA contents, respectively. The TAG profile of Jacu coffee was modified. TAG containing two saturated fatty acids were preferably hydrolyzed in detriment to those containing two unsaturated fatty acids. Other coffee components were not affected by the bird’s digestion of the beans. Kopi Luwak coffee samples had a chemical composition in accordance with reported ranges for non-bioprocessed green C. arabica samples, except for caffeine (0.48 g/100 g) and CGA (5.09 g/100 g), which were found in low amounts. Crop year rather than location or post-harvest processing discriminated Kopi Luwak coffee samples, suggesting that weather conditions would be the most crucial aspect for their chemical composition, especially in terms of total lipids, ashes, total CGA, sucrose and proteins.